2012
DOI: 10.1007/s00213-012-2707-z
|View full text |Cite
|
Sign up to set email alerts
|

Social rank, chronic ethanol self-administration, and diurnal pituitary–adrenal activity in cynomolgus monkeys

Abstract: Rationale Dominance hierarchies affect ethanol self-administration, with greater intake among subordinate animals compared to dominant animals. Excessive ethanol intake disrupts circadian rhythms. Diurnal rhythms of the hypothalamic–pituitary–adrenal axis have not been characterized in the context of ethanol self-administration with regard to social rank. Objective This study aimed to determine whether diurnal pituitary–adrenal hormonal rhythms account for differences between social ranks in ethanol self-adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 63 publications
6
34
1
Order By: Relevance
“…Lastly, no tolerance was observed in peak or nadir CORT following extended ethanol experience, supporting prior observations of a lack of neuroendocrine tolerance in animals with increasing BEC (Ogilvie et al, 1997). These effects are in contrast with studies in primates that revealed a mild attenuation of diurnal cortisol fluctuation, and a greater attenuation of diurnal ACTH rhythm following ethanol access (Cuzon Carlson et al, 2011; Helms et al, 2012). A major point of methodological difference is that in the primate studies, glucocorticoids were measured during 22 h access to voluntary ethanol intake; therefore longer duration of access and voluntary nature of ethanol experience may underlie the differences in plasma glucocorticoid changes.…”
Section: Discussioncontrasting
confidence: 98%
“…Lastly, no tolerance was observed in peak or nadir CORT following extended ethanol experience, supporting prior observations of a lack of neuroendocrine tolerance in animals with increasing BEC (Ogilvie et al, 1997). These effects are in contrast with studies in primates that revealed a mild attenuation of diurnal cortisol fluctuation, and a greater attenuation of diurnal ACTH rhythm following ethanol access (Cuzon Carlson et al, 2011; Helms et al, 2012). A major point of methodological difference is that in the primate studies, glucocorticoids were measured during 22 h access to voluntary ethanol intake; therefore longer duration of access and voluntary nature of ethanol experience may underlie the differences in plasma glucocorticoid changes.…”
Section: Discussioncontrasting
confidence: 98%
“…slightly lowered levels of ACTH and cortisol compared to saline self-administration (Broadbear et al 2005). Likewise, in monkeys that have chronically self-administered ethanol, and have habituated to awake blood sampling, ethanol self-administration resulted in decreased cortisol compared to pre-drinking baseline levels (Cuzon-Carlson et al 2011; Helms et al 2012a). Acute ethanol ingestion in humans (0.75 g/kg) did not increase ACTH or cortisol in most (6/8) young adult, nonalcoholic men (Waltman et al 1993).…”
mentioning
confidence: 99%
“…Using the same procedure as the present study, we previously reported that oral ethanol self-administration during a schedule-induced polydipsia procedure (Grant et al, 2008) flattens ACTH and blunts cortisol diurnal rhythms (Helms et al 2013). Subsequent ethanol self-administration (22 hours/day) resulted in a greater proportion of heavy drinkers that were of subordinate or intermediate compared to dominant social rank (Helms et al 2012a), which could be related to differences between social ranks in hormonal response to ACTH (Czoty et al 2009). Here we hypothesized that baseline HPA axis activity would correlate with the dose of self-administered ethanol, and the direction of correlation would depend on whether the neuroactive metabolites are positive or negative modulators of GABA A receptors (Figure 1).…”
mentioning
confidence: 99%
“…Although somewhat speculative at this point, it is tempting to suggest that the reduced sensitivity to alcohol we observed in socially isolated crayfish underlies the increase in drinking behavior that has been widely reported in socially isolated mammalian species (Wolffgramm and Heyne, 1991;Helms et al, 2012). If social isolation causes a suppression of the alcohol-induced acute neurobehavioral response, it would be reasonable to expect that humans and non-human animals increase drinking after social isolation (or 'exclusion') as a result of the lower sensitivity to the cellular effects of alcohol.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, other studies investigated how alcohol consumption is mediated by social factors; for example, subordinate rats and monkeys have been shown to consume significantly more alcohol than dominants (Blanchard et al, 1987;McKenzie-Quirk and Miczek, 2008), and rats and monkeys that were socially deprived (e.g. by housing them individually) also consumed more alcohol compared with animals housed in groups (Wolffgramm and Heyne, 1991;Helms et al, 2012). However, our understanding of the underlying mechanisms is still very limited, and it was recently suggested that in order to improve clinical relevance of addiction science, future studies should focus more specifically on the role of social context including factors such as social exclusion (Heilig et al, 2016).…”
Section: Introductionmentioning
confidence: 99%